Multinational enterprises from the Netherlands - Hoesel, Roger van, 1965-; Narula, Rajneesh, 1963- (Routledge studies in international business and the world economy, 1999)
Despite the long history of international economic activity and the dominant role of Dutch MNEs in the world economy there has been relatively little academic research in the area. This book explores issues such as: * What historical precedents underlie the character of Dutch MNE activity * How and why the technological specialisation of the Dutch economy and its firms has evolved to its current state * The changing FDI activity of Dutch MNEs * The strategic aspects of Dutch MNE activity in terms of location and R & D * The implications for Dutch MNEs of globalisation and eco.